The Effect of Learning Leadership Managerial at the State of Cikande Elementary School - Laela, Siti; Hanafi, Muhammad Syadeli; Sudadio, Sudadio (Jurnal Simki Pedagogia, 2023)
This study purpose is determined how to describe or provide an overview and relationship between learning leadership managerial at the state of Cikande Elementary School. The research method use a descriptive correlational research. It reveals whether there is a relationship between various variables based on the size of the correlation coefficient. The data obtained in the form of descriptive and numerical processing using statistical methods used and then interpreted. In this study, the population or research targets were all teachers at State Elementary Schools in Cikande District, Serang Regency. Based on data from the Department of Education and Culture of Serang Regency, there are 32 public elementary schools in the education sector, consisting of 306 teachers. The sample size calculation uses a table developed. From this calculation, 171 samples were obtained. The total population of 464 and the sampling technique used is proportional random sampling. This study uses SEM analysis tools using the Lisrel program. The methodologically of the research design is causal and simultaneous, has a relatively complicated relationship, so testing using this method is to be able to test what the objectives of this study are.The result show the managerial ability of the principal affects the quality of the school, learning leadership affects school quality and the feasibility of the facilities affects the quality of the school.